Methods for partial shading identification in photovoltaic panels of distributed generation: a brief literature review - Passos, Caroline Tedesco Santos; Ferri, Giovane Lopes; Fardin, Jussara Farias; Medina, Augusto César Rueda (Brazilian Journal of Production Engineering, 2024)
This article investigated methods for detecting and correcting faults caused by partial shading in solar panels. After reviewing various studies on strategies to mitigate the effects of shading on solar panels, it was concluded that there is a variety of computational approaches based on different algorithms, all aimed at maximizing energy efficiency. Complete elimination of shading is a complex challenge and still considered unattainable for various reasons. However, intelligent manipulation of shaded panels emerges as a promising and predominant strategy in current research as a way to overcome this limitation. This study contributes to understanding the available solutions for dealing with partial shading in solar panels and highlights the importance of energy efficiency as the main objective.